2010
DOI: 10.1371/annotation/4fd10061-5a1e-4164-833e-34943a74301c
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Modeling HIV Vaccines in Brazil: Assessing the Impact of a Future HIV Vaccine on Reducing New Infections, Mortality and Number of People Receiving ARV

Abstract: Background:The AIDS epidemic in Brazil remains concentrated in populations with high vulnerability to HIV infection, and the development of an HIV vaccine could make an important contribution to prevention. This study modeled the HIV epidemic and estimated the potential impact of an HIV vaccine on the number of new infections, deaths due to AIDS and the number of people receiving ARV treatment, under various scenarios. Methods and Findings:The historical HIV prevalence was modeled using Spectrum and projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Considering the number of people at risk of HIV infection in SSA, the economic benefit of an effective HIV vaccine could potentially dwarf the current estimates. Indeed, several modelling studies have shown that even a moderately efficacious HIV vaccine given to a limited number of people could still avert millions of new infections https://www.iavi.org/InformationCenter/ Publications/Documents/Global%20Impact%20Brief.pdf) [31].…”
Section: Why An Effective Hiv Vaccine Is the Most Preferred For Africamentioning
confidence: 99%
“…Considering the number of people at risk of HIV infection in SSA, the economic benefit of an effective HIV vaccine could potentially dwarf the current estimates. Indeed, several modelling studies have shown that even a moderately efficacious HIV vaccine given to a limited number of people could still avert millions of new infections https://www.iavi.org/InformationCenter/ Publications/Documents/Global%20Impact%20Brief.pdf) [31].…”
Section: Why An Effective Hiv Vaccine Is the Most Preferred For Africamentioning
confidence: 99%